Functional dissociation of stimulus intensity encoding and predictive coding of pain in the insula - Geuter, Stephan; Boll, Sabrina (eLife, 2017)
Pain processing in certain brain regions implements predictive coding principles, offering a novel perspective on the neural basis of pain perception.